The Role of Governmental Educational Institutions in Implementing Talents’ Development Programs in the UAE: An Explanatory Study - Younis, Basema (2019)
UAE educational institutions implement gifted and talented development programs; therefore, this study was the first to examine the application of these programs in UAE schools. The main research question of the study was to examine the efficiency of this implementation and the accuracy of outcomes of the applied programs over several stakeholders. The study adopted a qualitative explanatory method design to collect the data. The collection method included interviews with parents of the gifted and talented, teachers, programs’ managers, experts in the field, gifted and talented students and adults, in addition to a focus group with parents, teachers, and talented individuals A review of documents was also conducted. The conclusions highlighted diverse deficits in the implementation of several program components that have arisen from findings, and room for thorough improvement is necessary. The last chapter included a set of recommendations presented to better serve the highly able students in the UAE in future.